2017
DOI: 10.1007/s00455-017-9870-7
|View full text |Cite
|
Sign up to set email alerts
|

The Mendelsohn Maneuver and its Effects on Swallowing: Kinematic Analysis in Three Dimensions Using Dynamic Area Detector CT

Abstract: This study investigated the effects of Mendelsohn maneuver with three-dimensional kinematic analysis. Nine female speech-language pathologists (nine females, mean ± SD 27.1 ± 3.5 years old) underwent 320-row area detector scan during swallows of 4-ml nectar-thick liquid using with no maneuvers (control) and with Mendelsohn maneuver (MM). Critical event timing (hyoid, soft palate, epiglottis, laryngeal vestibule, true vocal cords (TVC), UES), hyoid and laryngeal excursion, cross-sectional area of UES, and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
2
18
0
4
Order By: Relevance
“…Inamoto and colleagues were able to perform a CT-based kinematic analysis of the swallowing act from the oral to the early oesophageal phase for the first time by using a scanner that enables the examination in a half-sitting position [ 103 ]. In initial studies, this technique was used to optimize the quantification of pharyngeal residues [ 104 ], to describe age-dependent changes in swallowing physiology [ 105 ] and to assess the influence of bolus volume [ 106 ], bolus viscosity [ 107 ] and swallowing maneuvers on the swallowing act [ 108 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Inamoto and colleagues were able to perform a CT-based kinematic analysis of the swallowing act from the oral to the early oesophageal phase for the first time by using a scanner that enables the examination in a half-sitting position [ 103 ]. In initial studies, this technique was used to optimize the quantification of pharyngeal residues [ 104 ], to describe age-dependent changes in swallowing physiology [ 105 ] and to assess the influence of bolus volume [ 106 ], bolus viscosity [ 107 ] and swallowing maneuvers on the swallowing act [ 108 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Yellow shows Annular flow and blue shows Plug flow Typical flow patterns in vertical flow. Adapted from[9]. Blue is liquid, white is air and surrounded an inner core of moving air.…”
mentioning
confidence: 99%
“…In addition to the movement parameters, supertasters had the shortest pharyngeal swallow phase duration (the time required to move the bolus through the pharynx), suggesting more efficient swallowing physiology than both mid-and nontasters. This may seem counterintuitive initially, and some studies have reported increased pharyngeal constriction to be associated with longer contraction of the relevant musculature (Inamoto et al, 2018;Molfenter et al, 2018). However, these findings involved within-subject comparisons of swallowing dynamics across varying conditions or cues that yielded different levels of effort in the swallows, i.e., the same basic motor plan executed to varying endpoints.…”
Section: Discussionmentioning
confidence: 99%